Analisis Faktor Penerimaan Sistem Pengelolaan Air Limbah Domestik Setempat Pada Permukiman Kumuh Tipologi Tepian Sungai Kota Pontianak - Amy Angelia; Prayatni Soewondo; Nico Halomoan; Prasanti Widyasih Sarli; Ahmad Soleh Setiyawan (Jurnal Serambi Engineering, 2024)
Slum areas in Pontianak, such as the Panglima A. Rani and Kayu Manis areas along the Kapuas River, face significant domestic wastewater management challenges, including river pollution and health issues. To meet the SDGs 2030, the city government plans to implement a domestic wastewater management system using both centralised and localised approaches. In this study, the Unified Theory of Acceptance and Use of Technology (UTAUT) and structural equation modelling (SEM) are used to analyse the factors influencing the acceptance of sanitation technologies. The research includes both quantitative and qualitative analyses using PLS-SEM in Smart PLS V.3.0. The results indicate that performance expectancy, effort expectancy, social influence and facilitating conditions influence community acceptance, with the highest path coefficients observed for facilitating conditions (41.26%), followed by social influence (32.19%), effort expectancy (21.46%) and performance expectancy (5.09%). Facilitating conditions and social influence have a significant impact on community participation, with P-values < 0.05 and T-statistic values > 1.96.